Determinants of socially responsible decisions among managers: a preliminary study - Alias, Siti Noormi; Ee, Min Jun; Omar, Zoharah (Human Resource Management Academic Research Society, 2019)
Despite of the arising number of studies on Corporate Social Responsibility (CSR), nevertheless, less research has explored individual factors influencing socially responsible decision among managers in Malaysia. Therefore, this preliminary study seeks to find the relationship between individual factors and socially responsible behavior among managers. A total of 73 respondents were selected though stratified random sampling method. The findings of the study revealed that all individual factors (empathic concern, internal locus of control and cognitive moral development) are positively correlated with socially responsible behavior and there are moderate and positive relationship between them. Meanwhile, among these individual factors, cognitive moral development was the most influential factors affecting socially responsible behavior among managers in Klang Valley. This study provides a support for the direction to Human Resource Development and Organizational Development practice based on Malaysian context. This study also supports the Theory of Planned Behavior and Stakeholder Theory on socially responsible behavior among managers in Klang Valley.